“Kartisampéka” Trigantalpati dalam Lakon Wayang Gandamana Tundhung Ki Hadi Sugito (“Kartisampéka” Trigantalpati in Gandamana Tundhung Shadow Puppet Play Performance by Ki Hadi Sugito) - Retno Dwi Intarti (Wayang Nusantara: Journal of Puppetry, 2020)
AbstractThis paper aimed to examine kartisampéka Trigantalpati in the Gandamana Tundhung play performed by Ki Hadi Sugito. Kartisampéka is an act of deluding others subtly and not automatically visible to other people (sinamun sinamudana). Kartisampéka has a negative connotation because the actions carried out are aimed at harming others. The data analysis was carried out by using descriptive analytical method. This study succeeded in finding kartisampéka as a sub-theme of the Gandamana Tundhung play performed by Ki Hadi Sugito. The kartisampéka concept which attached to the Trigantalpati character was used to build the plot for the Gandamana Tundhung play performed by Ki Hadi Sugito. AbstrakTulisan ini bertujuan mengkaji kartisampéka Trigantalpati dalam lakon Gandamana Tundhung Ki Hadi Sugito. Kartisampéka ialah perbuatan memperdaya orang lain secara halus dan tidak serta merta dapat dilihat oleh orang lain (sinamun sinamudana). Kartisampéka mengandung konotasi negatif, karena perbuatan yang dilakukan bertujuan mencelakakan orang lain. Analisis data dilakukan dengan metode deskriptif analitis. Kajian ini berhasil menemukan kartisampéka sebagai sub-tema dari lakon Gandamana Tundhung Ki Hadi Sugito. Konsep kartisampéka yang dilekatkan pada tokoh Trigantalpati digunakan untuk membangun plot lakon Gandamana Tundhung Ki Hadi Sugito.